PENGARUH KESADARAN WAJIB PAJAK, SANKSI PERPAJAKAN DAN PENERAPAN SISTEM E-FILING TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI: (Studi Pada KPP Mikro Piloting Majalengka) - Umam, Mochamad Febri Sayidil; Irfan Arifianto (JURNAL AKUNTANSI DAN SISTEM INFORMASI, 2023)
Abstract: This study aims to determine the effect of Taxpayer Awareness, Tax Sanctions, and the Implementation of the E-filing System on the Compliance of Individual Taxpayers registered at the KPP Mikro Piloting Majalengka. This study is a quantitative study using primary data with data collection techniques using a questionnaire measured using a Likert scale. The analytical method used is descriptive and verification analysis methods. The population of this study is an individual taxpayer registered at the KPP Mikro Piloting Majalengka as many as 264,884. The sampling technique in this study used a purposive sampling technique and the number of respondents determined using the Slovin formula was obtained as many as 100 respondents. The data analysis tool used is multiple linear regression data analysis technique with the SPPS version 25 program. The test results obtained in this study indicate that taxpayer awareness, tax sanctions, and partial application of the E-filing system all have a significant effect on individual taxpayer compliance.